Assays for cytokines and cytokine assay performance 1 - Whiteside, Theresa (Henry Stewart Talks, 2022)
The importance of measuring cytokines, Features of cytokines relevant to assays, Types of cytokine assays, Examples of most widely used cytokine assays, Principles of ELISA -Selecting the correct cytokine assay, Multiplex analyses and cytokine profiles